Research on Low-carbon Development Path of Coal-fired Power Industry - Chunsheng ZHAO; Junjun YANG; Jing WANG; Liqiang DUAN (发电技术, 2021)
The goal of "carbon peak, carbon neutrality" will have a profound impact on the coal-fired power industry, and reconstruct the industrial structure of the power industry. In view of the problems and challenges faced by the coal-fired power industry to achieve the dual-carbon target, it proposed to force the coal-fired power industry to transform through the final assessment results of carbon emission rather than impose a severe restriction on the development of coal-fired power industry. The coal-fired power industry will strive for more living space through low-carbon development paths, such as improving the energy efficiency of existing units, vigorously developing high-parameter generating units with high efficiency and ultra-low emission to replace small and medium-sized coal-fired units, actively promoting the application of low-carbon technologies, carrying out carbon neutralization and multi-generation, improving the flexible peak ability of coal-fired units, and strengthening the coupling development with renewable energy.